SIMULATION OF H2S DISPERSION USING COMPUTATIONAL FLUID DYNAMICS (Case Study at PLTP IV Pertamina Geothermal Energy Kamojang Area) - AKBARI DANASLA (NIM : 12811020), M.
Geothermal energy is a clean energy source which is being increasingly developed as part of an effort to decrease reliance on carbon based energy. One of company that developed geothermal energy in Indonesia is a PT Pertamina company that is PLTP IV PT Pertamina Geothermal Energy (PGE) Kamojang Area. Nevertheless, its development has some environmental impact with air pollution by Hydrogen Sulfide (H2S) that can be nuisance and its harmful for human health. The Observation data H2S concentration from PGE Kamojang Area shown increased of concentration at all cooling tower from 2012 - 2014 year. And then in 2014 year there have development with add 4 cooling tower at right side of first cooling tower. With this development that H2S concentration at PLTP IV PGE Kamojang Area likely will increase. Therefore, simulation of H2S dispersion is needed, then the result of simulation be able to use for early warning for decreasing impact of H2S. For simulation of H2S dispersion in this research is used one of model that is Computational Fluid Dynamics (CFD) model. CFD model is very useful to analyze problem that related with fluid flow, including H2S dispersion which leak out by cooling tower. On scenario 1 is simulation with 4 cooling tower found that the dangerous time are when morning and night because H2S consentration tend to high and maximum, while the safely time is when afternoon because H2S concentration tend to lower. Meanwhile on scenario 2 is simulation with 8 cooling tower found that added 4 cooling tower made H2S concentration at point of study increased than before added. The increased of H2S concentration that happened up to 61%.